2016
DOI: 10.1097/md.0000000000003281
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Retinal Artery Occlusion in Patients With End-Stage Renal Disease

Abstract: There is globally increasing prevalence and incidence in end-stage renal disease (ESRD). These patients are frequently reported to have retinal abnormalities and both diseases share some systemic risk factors. Hence, it is clinically relevant to determine whether ESRD is a predictor of retinal artery occlusion (RAO).To investigate the risk of RAO in ESRD patients.A retrospective, nationwide, matched cohort study. The study included 93,766 ESRD patients recruited between 2000 and 2009 from the Taiwan National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The total sugar contents of Nitraria species were found to be lower as compared to Nitraria of Qinghai origin (6.81-7.06 %). A higher total fat range (3.86-4.12 %) was reported previously [32]. The overall results showed that the fruit could be a potential source of sugar, flavonoid and total fat.…”
Section: Resultssupporting
confidence: 68%
“…The total sugar contents of Nitraria species were found to be lower as compared to Nitraria of Qinghai origin (6.81-7.06 %). A higher total fat range (3.86-4.12 %) was reported previously [32]. The overall results showed that the fruit could be a potential source of sugar, flavonoid and total fat.…”
Section: Resultssupporting
confidence: 68%
“…Some studies have reported that several comorbidities, such as hypertension, hyperlipidaemia, congestive heart failure, coronary artery disease, and chronic renal failure, are associated with RAO, a vision-threatening retinal vascular disease [ 12 , 42 44 ]. In this cohort study, we evaluated these comorbidities in patients with DM and found that hypertension was the only significant risk factor for RAO in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The study has high statistical power and increased precision in risk appraisal because it is based on a nationwide population-based dataset, including a large sample of patients with ESRD on dialysis. Several previous studies using the same database have already been published [ 9 , 32 , 33 ]. Furthermore, our study is a cohort study analysing the incidence of serous retinal detachment in patients with ESRD on dialysis, with comparisons between cohorts over a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwan has the highest incidence and prevalence of patients with ESRD on dialysis [ 6 8 ]. Furthermore, the association between ESRD and many retinal diseases, such as retinal artery occlusion, retinal vein occlusion, or age-related macular degeneration, has been demonstrated by several reports recently [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%